Selectivity versus Sustainability of Refugee Return - Mesić, Milan, sociolog (Array, 2009)
The devastating conflicts in former Yugoslavia resulted in a large number of erfugees. The authors analyse the possibilities of sustainable return of the Serb minority that flad from Croatia. They demonstrate the importance of the situation in the former homes of the refugees, that is, how policies of economic and infrastructural development may facilitate return. At the same time, they also discern an important difference among the age groups of the refugees ; the educated and urban young people see a better future for themselves in their countries of residence, while the older refugees, especially those from the countryside and with less education, are more likely to return.